Characteristics of IL‐25 and allergen‐induced airway fibrosis in a murine model of asthma. Issue 5 (30th April 2015) - Yao, Xiujuan; Wang, Wei; Li, Yan; Lv, Zhe; Guo, Run; Corrigan, Chris J; Ding, Gang; Huang, Kewu; Sun, Yongchang; Ying, Sun
Abstract Background and objective Interleukin (IL)‐25 has been implicated in the pathogenesis of human asthma by inducing a Th2 cytokine response, but its possible role in the development of airway remodelling is less clear. Methods We developed a murine surrogate of chronic airway inflammation induced by intranasal application of IL‐25 alone. Comparison was with the 'classical' surrogate of ovalbumin (OVA) intranasal instillation into previously sensitized animals. Airway fibrotic biomarkers were analysed by immunohistochemistry and enzyme‐linked immunosorbent assay. Additionally, proliferation assay and real‐time polymerase chain reaction analysis were performed to assess IL‐25's effects on primary human bronchial fibroblasts in vitro. Results In Balb/c mice, intranasal instillation of IL‐25 alone induced florid airway fibrosis, including increased lay down of extracellular matrix proteins such as collagen I, III, V and fibronectin, increased numbers of fibroblasts/myofibroblasts, a profibrotic imbalance in matrix metalloproteinase/tissue inhibitor of metalloproteinase production and increased expression of profibrotic mediators including connective tissue growth factor and transforming growth factor‐β1. These changes broadly reproduced those seen with classical intranasal OVA challenge in OVA‐sensitized animals. Furthermore, IL‐25 induced proliferation and expression of collagen I and III and smooth muscle α‐actin in primary human lung fibroblasts. Conclusions We conclude that chronic exposure of the airways to IL‐25 alone is sufficient to cause functionally relevant airway remodelling, with the corollary that targeting of IL‐25 may attenuate bronchial remodelling and fibrosis in human asthmatics.